Child Death Disclosure - Standardized Patient Case - Jeffrey Siegelman; Paul DeSandre; Tammie Quest (Association of American Medical Colleges, 2015)
Abstract Introduction Delivering a death disclosure is a routine yet high-stakes part of the practice of an emergency physician. However, this is a skill that is practiced with a wide range of competence by both residents and faculty, and one that can be improved through practice. This resource is a standardized patient scenario created to teach emergency medicine interns how to deliver a death disclosure in the case of a child. This case was created as part of a hands-on session for emergency medicine interns to increase their comfort and competence with death disclosures. Communication skills necessary for such a conversation are a focus of the Accreditation Council for Graduate Medical Education milestones in emergency medicine. Methods There is clear evidence describing validated methods of delivering this information to patients and families. However, there is a dearth of published cases to use for practice with standardized patients with faculty observing. This resource includes all necessary material needed to implement a standardized patient scenario. An assessment form is also included, and can be adapted for use by either a standardized patient or faculty rater. Results This case was implemented for interns in the final month of internship as part of a day-long session in death disclosure skills. Following implementation, feedback from interns was positive, in that most enjoyed the experience and found it to be a valuable use of resources. In addition, most were able to utilize the death disclosure construct that was taught in the morning didactic session. Discussion The session length was appropriate for the case and debriefing. While there is literature supporting certain methods of death disclosure, there are few published cases for implementation with standardized patients.